Food handler knowledge, attitude and practice in school canteen / Nur Lyana Amira Zainal Azlan & Nurul Azwani Aladin - Zainal Azlan, Nur Lyana Amira; Aladin, Nurul Azwani (2017)
This research is about food handler knowledge, attitudes and practice at school canteen. The purpose of this study is to determine the food handler knowledge, attitudes and practices at the school canteen and to identify the barrier among food handler in school canteen in implementing knowledge, attitudes and practices. Food handler is someone who is very important in determining the safety of food. Food handlers should received the training in food safety to increase their knowledge. Educational effort and with supportive manager have a great potential to improve food handlers knowledge, attitudes and practices. Close cooperation between Ministry of Health, the Ministry of education and local government also is needed to ensure that the food handler are being trained. Nowadays, many cases of food borne illness occur in the institutional foodservice industry especially in school. Food poisoning cases among student increase each year.. All this cases happened, because of the barrier that occurred among food handler. They cannot avoid this barrier because of the culture and habit among them. This study was used secondary data where the information obtain was already documented, analysed and gather with other people. The information was get from the previous journal, UiTM Online Library, EzAccess, Science Direct, Google Scholar and reading sources such as books and dictionary.